Atrial fibrillation: Epigenetic aspects and role of sodium-glucose cotransporter 2 inhibitors. (February 2023) - Donniacuo, M.; De Angelis, A.; Telesca, M.; Bellocchio, G.; Riemma, M.A.; Paolisso, P.; Scisciola, L.; Cianflone, E.; Torella, D.; Castaldo, G.; Capuano, A.; Urbanek, K.; et al.
Abstract: Atrial fibrillation (AF) is the most frequent arrhythmia and is associated with substantial morbidity and mortality. Pathophysiological aspects consist in the activation of pro-fibrotic signaling and Ca 2+ handling abnormalities at atrial level. Structural and electrical remodeling creates a substrate for AF by triggering conduction abnormalities and cardiac arrhythmias. The care of AF patients focuses predominantly on anticoagulation, symptoms control and the management of risk factors and comorbidities. The goal of AF therapy points to restore sinus rhythm, re-establish atrioventricular synchrony and improve atrial contribution to the stroke volume. New layer of information to better comprehend AF pathophysiology, and identify targets for novel pharmacological interventions consists of the epigenetic phenomena including, among others, DNA methylation, histone modifications and noncoding RNAs. Moreover, the benefits of sodium-glucose cotransporter 2 inhibitors (SGLT2i) in diabetic and non-diabetic patients at cardiovascular risk as well as emerging evidence on the ability of SGLT2i to modify epigenetic signature in cardiovascular diseases provide a solid background to investigate a possible role of this drug class in the onset and progression of AF. In this review, following a summary of pathophysiology and management, epigenetic mechanisms in AF and the potential of sodium-glucose SGLT2i in AF patients are discussed. Graphical Abstract: ga1